THE IMPORTANCE OF TRANSLATION - Yu. Ch. Mehmonova; M. Jo’raqulova (Web of Journals Publishing, 2024)
This article focuses more on idiomatic expressions, collocations and phrases as well as their adequate in target language, ways of translation and main techniques of translation.
Keywords: lexical phrases, functional semantics, pragmatics, phraseology.